PHYSICAL ACTIVITY CRISIS AMONG PHYSICAL EDUCATION STUDENTS: EMPIRICAL EVIDENCE FROM A SURVEY OF PHYSICAL ACTIVITY AMONG PJOK STUDENTS IN THE ERA OF SEDENTARY LIFESTYLES - I Made Dwi Sastra Wargama; Wayan Kristin; Irfandi Irfandi (Jurnal Penjaskesrek, 2026)
Physical activity is essential for overall health, yet it is declining among university students due to academic pressures, technological use, and sedentary lifestyles. This study aimed to describe physical activity levels among Physical Education students and examine their relationship with sedentary behavior, motivation, and perceived impacts. A quantitative cross-sectional survey was conducted with 118 students using a 17-item Likert-scale questionnaire. Data were analyzed descriptively through scoring, frequency, and percentage. The findings show that physical activity levels are generally moderate, while sedentary behavior is moderate to high. Motivation tends to be low to moderate, and many students report notable physical and psychosocial effects. These results indicate a multidimensional physical activity crisis and a gap between students’ academic roles and daily practices. The study highlights the need for comprehensive and sustainable campus-based interventions to promote active lifestyles.